3D cell culture model: From ground experiment to microgravity study - Ma, Chiyuan; Duan, Xianglong; Lei, Xiaohua (Frontiers in Bioengineering and Biotechnology, 2023)
Microgravity has been shown to induce many changes in cell growth and differentiation due to offloading the gravitational strain normally exerted on cells. Although many studies have used two-dimensional (2D) cell culture systems to investigate the effects of microgravity on cell growth, three-dimensional (3D) culture scaffolds can offer more direct indications of the modified cell response to microgravity-related dysregulations compared to 2D culture methods. Thus, knowledge of 3D cell culture is essential for better understanding the in vivo tissue function and physiological response under microgravity conditions. This review discusses the advances in 2D and 3D cell culture studies, particularly emphasizing the role of hydrogels, which can provide cells with a mimic in vivo environment to collect a more natural response. We also summarized recent studies about cell growth and differentiation under real microgravity (RMG) or simulated microgravity (SMG) conditions using ground-based equipment. Finally, we anticipate that hydrogel-based 3D culture models will play an essential role in constructing organoids, discovering the causes of microgravity-dependent molecular and cellular changes, improving space tissue regeneration, and developing innovative therapeutic strategies. Future research into the 3D culture in microgravity conditions could lead to valuable therapeutic applications in health and pharmaceuticals.